Studi Analisis Kualitas Air dan Potensi Pembentukan Asam pada Batuan di Universitas Bangka Belitung - Delita Ega Andini (PROMINE, 2017)
The condition of water, soil and rock in Bangka Belitung University can be one of reference forconservation area and future development. Field observation known that the research location isgrouped into formation of sedimentary is Tanjung Genting Formation. Average pH of water 5,3; TDS41.1 mg/l; TSS 11,1 mg/l and Al content 0,18 mg/l; Fe 0.32 mg/l; Cu 0.14 mg/l taken from groundwaterand surface water samples. Rock samples of static test results obtained that the rocks are acidic butinto the category is uncertain. However, from the paste pH it was found that the pH of rocks is 5,39and this shows that the rocks are not potentially acidic.